Training load and fitness monitoring in Czech football: coach practices and perspectives - Bokůvka, Dominik; Hrubý, Michal; Čuperková, Kristýna; Vencúrik, Tomáš; Padinha, Vitor; Paludo, Ana Carolina (Frontiers in Sports and Active Living, 2025)
IntroductionThe study aimed to describe the practices and perspectives of Czech football coaches regarding the monitoring of players’ training load and physical performance, with a focus on identifying key barriers and preferred sources of information.MethodsA total of 235 football coaches completed an online survey comprehending training load monitoring methods, physical performance assessments, barriers to implementation, and information sources.ResultsAmong respondents, 93.7% reported monitoring training load, with training diaries (70%) being the most utilized method for external load measures and heart rate (45%) for internal load. Despite this, 42.7% of coaches did not monitor internal load and 21.7% did not conduct physical fitness evaluations. The most frequently reported barrier was a lack of resources (74.5%), though elite-level coaches (52.8%) and strength and conditioning coaches (75%) identified human resources as their primary limitation. Across all levels, the Football Association was the preferred source of information (61.7%).ConclusionThe findings highlight the predominance of traditional monitoring practices among the Czech football coaches, alongside with notable gaps in internal load tracking and fitness evaluation. The resource constraints remain a major barrier. Practical recommendations include promoting economical monitoring tools, such as RPE, and enhancing collaboration among stakeholders to improved monitoring strategies. The Football Association's play a key role on support these efforts.